Model Penanganan Anak Berkebutuhan Khusus Pada Sekolah SLB Osakali Kecamatan Pulau Bandring Kabupaten Asahan - Syahrizal Syahrizal; Aisyah Eka Suci; Eva Khairani (Pusdikra Publishing, 2022)
The purpose of this study is to find a model the handling of children with special needs in great schools Osakali Asahan, knows all the barriers experienced in the process of handling children with special needs disabled athletes, and know that a solution done in the face of obstacles the handling of children with special needs disabled athletes. This research as the subject of research or sources is a head of school, and many of the teachers who used a qualitative approach through the method of analysis deskrptif. As for data collection techniques which was conducted through a, observation, interview, research and documentation to the subject. This research result indicates three (3) point it, first is a model handling children with special needs disabled athletes in special needs schools osakali asahan is by using extraordinary primary school, where a model his service use education services such as the school usual or regular consisting of various levels from the base up to a higher level, and children handled in accordance with abnormalities or disability each. which are (1) lacking facilities and infrastructure supporting in the form of classrooms and there is little media, (2) a lack of Children with special needs disabled athletes and teachers skill owned, (3) the stigma of the community pertaining to children with special needs disabled athletes who are still viewed rendeh because he could not do anything and in also did not send a lot of changes. Third , solutions to deal with the obstacles in handling their children with special needs indonesian is as follows:(1) increases the total number of teachers children with special needs disabled athletes and increase the quality of them with various education intervention and training related, (2) teachers should look to be creative use of existing infrastructure by making media itself that is easy to understand students , (3) give the understanding of to the community, including parents student guardians will important education for babies to Children with special needs disabled athletes having confidence,self help, and able to hang out with the other normal.